Using Case Studies to Promote Student Engagement in Primary Literature Data Analysis and Evaluation - Cook-Snyder, Denise R. (J Undergrad Neurosci Educ, 2017)
Analyzing and evaluating primary literature data is a common learning objective in undergraduate neuroscience courses. However, students with more clinically focused career goals often dismiss the relevance of evaluating basic neuroscience literature. Here, we describe using case studies to promote student engagement in primary literature in a cellular and molecular neuroscience course. Two example literature-based case studies are provided: Untwisting Pretzel Syndrome, a neurodevelopment case exploring synapse formation in a pretzel syndrome patient, and The Trials of ALS, a neurodegeneration case exploring axon degeneration and repair in an amyotrophic lateral sclerosis patient. These cases were assigned after neurodevelopment and neurodegeneration lectures covering key concepts. Both cases begin by introducing the patient and hypothesizing symptoms and diagnoses, followed by scenes incorporating primary data to illustrate disease pathogenesis and treatments. Students complete questions embedded in these cases as homework, and class time is used to discuss their answers. Discussion emphasizes that there can be multiple “correct” answers, and the best answers are accurate and well-supported. Accordingly, students edit their answers in class, and these annotations are factored into a pass/fail grade on the case. Additional scenes and questions from the same case studies are used on the course’s take-home exams, thereby allowing students to practice primary data analysis and evaluation before a graded assignment. Student evaluations support literature-based case studies as an effective learning tool, with students identifying cases as the most valuable aspect of the course, and reporting increased confidence in understanding cellular and molecular neuroscience.